Management of Islamic Religious Education Values Implementation for Students with Autism: A Case Study at SLB Nur Asih Bintaro - Pratama, kahfi; Fauzi, Anas; Abdul Jamil, Hasim (Faiyadhah | Journal of Islamic Education Management, 2025)
This study aims to analyze in-depth the management of planning, implementation, and evaluation in instilling Islamic educational values in autistic students at Nur Asih Special Needs School. Islamic education for children with special needs, especially autistic children, requires a different and more personalized approach compared to children in general. Therefore, the planning, implementation, and evaluation processes must be carried out carefully and tailored to the unique characteristics of each individual. This study used a qualitative approach with a case study method, with data collection techniques through in-depth interviews with the principal, class teachers, and Islamic religious education teachers at Nur Asih Special Needs School. The results show that in the planning stage, the school has adapted the curriculum to suit the needs, potential, and limitations of autistic students, and inserted Islamic values ​​gradually and contextually. In the implementation stage, the learning methods used are flexible and adaptive, such as individual learning, the use of visual media, and direct practice in religious activities such as congregational prayer, daily prayer habits, and gradual learning of the Quran. Evaluation is carried out periodically by paying attention to the development of cognitive, affective, and psychomotor aspects of students. Evaluation also serves as the basis for providing remedial and enrichment programs. The values instilled include aspects of akidah (faith), ibadah (religious practice), and akhlak (daily behavior), with the ultimate goal of developing a strong and contextual Islamic character in the lives of autistic students. This study emphasizes the importance of synergy between schools, families, and the surrounding environment in supporting successful learning. The results are expected to serve as a reference for other educational institutions in implementing inclusive, effective, and sustainable Islamic education management for children with special needs.